Optimisation of vancomycin exposure in neonates based on the best level of evidence. (April 2020) - Dao, Kim; Guidi, Monia; André, Pascal; Giannoni, Eric; Basterrechea, Sébastien; Zhao, Wei; Fuchs, Aline; Pfister, Marc; Buclin, Thierry; Csajka, Chantal
Graphical abstract: Abstract: There is no consensus regarding optimal dosing of vancomycin in term or preterm neonates. Various available dosing recommendations are based on age, kidney function and/or body weight to define a starting dose. Our objectives were (i) to develop a comprehensive population PK model of vancomycin in a large cohort of neonates and (ii) to evaluate and compare the performances of current dosing approaches with respect to target attainment, using simulations based on our model. This will serve the purpose to recommend the best dosing approaches among existing regimens in the early and later phases after treatment initiation as a complementary approach to therapeutic drug monitoring (TDM). A total 405 neonates provided 1831 vancomycin concentrations measured during routine TDM. A one-compartment model with linear elimination incorporating covariates such as age, kidney function and body weight was developed (NONMEM®). The final model was applied to simulate in our population vancomycin exposure resulting from 20 dosing guidelines identified in the literature. Proportions of patients within and above target exposure were used as a performance measure. Target attainment meant area under the curve/minimal inhibitory concentration (AUC24 /MIC) ratio of 400–700 h and trough concentration of 10–20 mg/L, both on days 1 and 7. Most current vancomycin dosing regimens fail to ensure target attainment in a majority of neonates. Insufficiently dosed regimens should be avoided, especially in centers with widespread coagulase negative Staphylococci. Adding a loading dose to simple regimens is best recommended to increase the proportion of early target attainment. Complex regimens seem to marginally improve exposure. Optimisation of efficacy while minimizing toxicity of vancomycin in neonates is needed. The application of a simple dosing regimens like NNF7 or the Neofax Hi-Dose regimens, with a 25 mg/kg loading dose for severe infections, or the SmPC regimen should be recommended to ensure the highest proportion of target attainment after 24 h. TDM should then be carried out, to account for residual unexplained variability in vancomycin elimination.